(untitled) (Studia Prawnicze / The Legal Studies, 2023)
W obecnej sytuacji gospodarczej w państwie, budownictwo ze środków własnych społeczeństwa staje się coraz większym wyzwaniem. Pomoc kredytowa państwa zależy od formy spółdzielczości budownictwa mieszkalnego. Zgodnie z ustawą z dnia 17 lutego 1961 r, o spółdzielniach i ich związkach wyróżniamy: spółdzielnie mieszkaniowe (lokatorskie), budowlano-mieszkaniowe (własnościowe) oraz spółdzielcze zrzeszenia budowy domów jednorodzinnych. Autor artykułu przedstawia pojęcie spółdzielczego prawa do lokalu zgodnie z regulacjami zawartymi w ww. ustawie oraz kodeksie cywilnym. Opisuje moment powstania spółdzielczego prawa do lokalu, w którym wyróżnia charakterystyczne elementy. Charakteryzuje treść i wykonywanie spółdzielczego prawa do lokalu, w jaki sposób można nim rozporządzić. Ponadto, porusza kwestie dotyczące zbycia, dziedziczenia, egzekucji oraz wygaśnięcia tego prawa. In the current economic situation in the state, building with the use of public funds is becoming increasingly challenging. State credit assistance depends on the form of housing cooperatives. According to the Act of 17 February 1961 on cooperatives and their associations, we distinguish between: housing cooperatives (tenant-based), building cooperatives (ownership-based) and cooperative housing associations. The author of the article presents the concept of the cooperative right to premises in accordance with the regulations contained in the aforementioned Act and the Civil Code. He describes the moment when the cooperative right to premises is created, in which he distinguishes the characteristic elements. He characterises the content and exercise of the co-operative housing right, how it can be used. In addition, he addresses issues concerning the disposal, inheritance, enforcement and termination of this right.